Electro-mechanical impedance and wave propagation modeling of piezoceramic transducers - Hu, Yuhang. (2008)
The advent of smart materials, such as LEAD Zirconate Titanate (PZT), has ushered a new era in the field of structural health monitoring (SHM). The new SHM technique in virtue of PZT transducers, because of many advantages such as autonomous, real- time, online and remote monitoring, may provide a cost-effective alternative to the conventional SHM techniques.